Basophil CD63 expression in chronic spontaneous urticaria: correlation with allergic sensitization, serum autoreactivity and basophil reactivity. (5th September 2016) - Chen, Q.; Zhai, Z.; Xu, J.; Chen, W.; Chen, S.; Zhong, H.; Huang, X.; Hao, F.; Song, Z.
Abstract: Background: The underlying causes and factors contributing to the disease severity of chronic spontaneous urticaria (CSU) are unknown. Objective: Given the important role of basophils in the pathogenesis of urticaria and that CD63 serves as a useful marker for basophil activation and detecting, CD63 expression of basophils is a reliable tool for diagnosing allergy and hypersensitivity reactions to different allergens; the objective of this study was to investigate whether the level of basophil CD63 expression is correlated with allergen sensitization, serum autoreactivity and basophil reactivity in patients with CSU. Methods: Basophil‐enriched leucocytes were separated from the blood of 64 patients with chronic urticaria (54 CSU patients and 10 symptomatic dermographism patients), 18 healthy control subjects and seven atopic donors without urticaria. Flow cytometry was then used to detect CD63 expression on the cell membrane of basophils from all samples. Analysis was also preformed on basophils incubated with sera from CSU patients with positive or negative autologous serum skin test (ASST). Results: CD63 expression was significantly higher in the basophils from patients with CSU than in those from patients with symptomatic dermographism and the healthy control group. The levels of CD63 expression in CSU patients with ASST + and/or allergen sensitization were higher than those with ASST − and/or no allergen sensitization patients. Incubation with ASST + serum resulted in an increased expression of CD63 in the basophils of ASST + CSU patients, whereas no such response was observed in healthy controls or ASST − CSU patients. Conclusion: The increased CD63 expression in basophils from CSU patients may correlate with allergen sensitization, autoreactivity of serum and basophil reactivity. Our results suggest that CD63 may contribute new insight into the pathogenesis of CSU.